Analysis of The Implementation of Pharmaceutical Service Standards at Granmed Lubuk Pakam Hospital - Jhoti Sumitra; Miftahul Jannah; Yosi Darmirani (Jurnal FARMASIMED (JFM), 2026)
Background: Pharmaceutical care involve direct interaction and responsibility of pharmacists to patients regarding pharmaceutical products with the aim of achieving clear outcomes to improve patients' quality of life. To enhance the quality of pharmaceutical care in hospitals, the Minister of Health Regulation No. 72 of 2016 on Standards of Pharmaceutical Services in Hospitals was established. Pharmacists have the duty to provide advice, information, and education related to the medications received by patients, as well as assist patients in implementing a healthy lifestyle to ensure the success of the treatment. They also monitor the outcomes of the therapies that patients have undergone and collaborate with other healthcare professionals with the goal of improving patients' quality of life. Objective: To analyze the implementation of the Minister of Health Regulation No. 72 of 2016 on Standards of Pharmaceutical care Hospital in relation to patient satisfaction. Method: cross-sectional in nature. The collected data were compared with standards listed in the literature and analyzed using the Chi-Square method. Results: it was found that 25 individuals (42.4%) who responded felt that clinical pharmacy services were unsatisfactory, while 34 individuals (57.6%) felt that the clinical pharmacy services were quite good. Conclusion: the implementation of PMK No. 72 of 2016. There is a relationship between clinical pharmacy care and patient satisfaction at Granmed Lubuk Pakam Hospital (p value = 0.007).